EFFECTS OF CURRENCY OUTSIDE BANKS ON REAL ECONOMIC GROWTH IN NIGERIA (Journal of the Management Sciences, 2024)
In the figures released by the Central Bank of Nigeria (CBN) in November, 2023, about 92% of currency in circulation (CIC) in Nigeria is outside the banking system. Obviously, this is a source of concern to the regulatory authorities. Some questions readily cme to mind in this regard - Does it mean that Nigerians no longer save their monies in banks or is it that they are investing into the economy. If the later is the case, then the Nigerian economy is better off for it. Thus, this study is set to ascertain the effects of currency outside banks (COB) on real economic growth in Nigeria. Varied econometric tests were carried out. .Outcome of the study revealed that Currency outside bank has a negative but not significant relationship with Real Gross Domestic Product. Pairwise Granger Causality test indicates that no causality was established between Currency outside banks and Real Gross Domestic Product. This implies that Currency outside banks did not influence Real Gross Domestic Product in Nigeria and vice versa for the period under review. However, the above results should be interpreted with caution as more Nigerians now prefer to keep money at home instead of banks for some obvious reasons that range from greed, corruption and loss of confidence in the Nigerian banking sector .Other reasons include poor banking services, instability of the financial sector and the political class who had stolen public funds, they need a safe haven for their loot which the conventional banks cannot offer them. The study therefore recommends that government should design policies to encourage and to incorporate financially excluded economic agents controlling huge chunks of funds outside the formal financial system. This is with the aim of contributing to economic growth, development and improved financial deepening in Nigeria.
Keywords: Currency outside Banks, Currency in Circulation, Embezzled Funds, and Real Economic growth.